Flow and fiber orientation of fresh fiber reinforced concrete. Issue 1 (14th December 2021) - Gerland, Florian; Schomberg, Thomas; Kuhl, Detlef; Wünsch, Olaf
Abstract: The orientation of the fibers in UHPC is decisive for the tensile strength and failure of the components. The mold filling strategy during casting of structural components dictates the flow routing and thus the fiber orientation. In addition, the orientation of the fibers also affects the flow behavior of the suspension. In measurements of rheological properties in concrete rheometers, strongly scattering measurements often occur. In this paper, a novel fiber orientation model for viscoplastic fluids is investigated in Couette flow. The effect of the fibers on the flow condition and the measurable torque is described. The results of the numerical investigation give indications for increasing the reproducibility of rheological measurements on fresh fiber concrete.